Apakah Biaya Kualitas Penting Meningkatkan Keunggulan Kompetitif dan Kinerja Organisasi - Zul Azmi; Siti Samsiah; Sulistyandari Sulistyandari (Akuntansi & Ekonomika, 2022)
SMEs can achieve competitive advantage by paying attention to quality cost management. This research investigates the effect of quality costs (prevention, assessment, failure) on the competitive advantage and performance of SMEs in Pekanbaru City. A total of 278 SME business populations in the food and beverage category were then selected using purposive sampling. 139 questionnaires were distributed to owners or management of SMEs and as many as 85 respondents participated and were processed in this study. By using path analysis, the result shows that quality costs affect competitive advantage. Cost of quality also has a significant effect on the performance of SMEs in the city of Pekanbaru. Competitive advantage mediates the relationship between quality costs and performance.